The role of the special education teacher in building and inclusive school - Pinho, I. (2021)
Ensuring that all students have access to quality education is also recognizing the intrinsic value of diversity and respect for the dignity of the human person [1]. In this sense, concerning the inclusion of students with special educational needs, this is a process often seen as the exclusive responsibility of the Special Education teacher. Assuming the importance of the Special Education Teacher (SE) role in the construction of a school that wants to be inclusive, this article aims to assess: 1 how the SE teacher works in schools; 2 how the work related to Special Education is organized and 3 what is the opinion of teachers about legislation related to Special Education. The methodology adopted in this study took a qualitative approach, using semi-structured interviews as the data collection technique. The study was carried out in seven school groups, involving ten teachers (n = 10) specialized in Special Education. Main results point to the fact that SE teachers identify several constraints to the promotion of a school that intends to be more inclusive, namely, lack of resources, ineligibility to support students with problems such as hyperactivity disorder and attention deficit and lack of connection between SE teachers and regular schoolteachers. In general, a Special Education teacher often has a supportive role only to the student, lacking articulation with regular education teachers so that they develop inclusive practices for all students, given global success.